2019
DOI: 10.1088/1757-899x/518/3/032045
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Dry Sliding Wear for Aluminium Bronze Alloy Reinforced by Al2O3 and TiO2 Nanoparticles

Abstract: In this investigation deals with a dry sliding wear of Aluminium bronze alloy reinforced by nanoparticles of α-Al2O3 and Rutile-TiO2. Stir casting method was used by induction furnace to increase wettability between nanoparticles and melting matrix. The copper base alloys reinforced with different percentages of (1.5 and 3 weight percent) of nanoparticles α-Al2O3 and Rutile-TiO2 separately and together. These samples were tested to investigate wear behaviour, using Ball-on-Disc technique, and examined with som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Wear tests were performed using a block-on-ring wear testing device with 0.2 ms −1 sliding velocity, four different sliding distances (400 -1600 m) and three different loads (10 N, 20 N and 30 N) and it was found that increasing the iron content increases the hardness of aluminium bronze with highest hardness value of 55.74HV observed. Generally, iron and nickel enriched aluminium bronze has lower hardness as compared to aluminium bronze strengthed with nanoparticles, comparing with results from Ajeel et al [85]. However, iron and nickel enriched aluminium bronze has a much lower friction coefficient of 0.02 to 0.04 under approximately similar testing conditions.…”
Section: Aluminium Bronze Alloysupporting
confidence: 71%
See 2 more Smart Citations
“…Wear tests were performed using a block-on-ring wear testing device with 0.2 ms −1 sliding velocity, four different sliding distances (400 -1600 m) and three different loads (10 N, 20 N and 30 N) and it was found that increasing the iron content increases the hardness of aluminium bronze with highest hardness value of 55.74HV observed. Generally, iron and nickel enriched aluminium bronze has lower hardness as compared to aluminium bronze strengthed with nanoparticles, comparing with results from Ajeel et al [85]. However, iron and nickel enriched aluminium bronze has a much lower friction coefficient of 0.02 to 0.04 under approximately similar testing conditions.…”
Section: Aluminium Bronze Alloysupporting
confidence: 71%
“…The friction coefficient of aluminium bronze under normal loading and sliding against mild steel is generally within 0.01 to 0.25 under greased or oiled conditions [83,84]. Aluminium bronze alloy is usually strengthened with nanoparticles of aluminium oxide, titanium dioxide [85] or higher composition of iron and nickel [86] as it was found that these oxide dispersions strengthened alloys or iron-nickel enriched copper alloys tend to have higher elevated thermal stability, increased hardness and improved creep resistance which are properties more suitable for dry sliding applications [87,88].…”
Section: Aluminium Bronze Alloymentioning
confidence: 99%
See 1 more Smart Citation